Curriculum Management of Package C Equivalent Program in Preparing Graduates Ready to Work in PKBM Alam Rumah Matahari Sukodono Sidoarjo - Ni'matul Fauziyah; Lilik Huriyah; Ibrahim, Abdullah Malik (PT Ilmu Inovasi Nusantara, 2024)
The high unemployment rate in Indonesia is partly due to limited access to education. The Package C equivalency program at PKBM Alam Rumah Matahari offers a non-formal education solution that is an alternative for people who have not completed formal education and also prepares graduates for the world of work. This study analyzes the management of the Package C curriculum at PKBM Alam Rumah Matahari Sukodono Sidoarjo in preparing graduates for the world of work. This study uses a descriptive qualitative method with observation, interview, and documentation data collection techniques. The data is then analyzed using Milles and Huberman's analysis techniques, namely data collection, data reduction, data presentation, and drawing conclusions to obtain valid data. The results of the study show that curriculum management includes planning, organizing, implementing, and evaluating which are adjusted to the needs of students and the world of work. Government funding support, infrastructure, and implementation of the Merdeka Belajar Curriculum are the main supporting factors. However, challenges such as low student attendance and public views on PKBM need to be overcome. The impact of this curriculum can be seen from its graduates who are able to become entrepreneurs or work in the government sector. Optimization of curriculum management and increasing public awareness need to be strengthened so that Package C graduates are better prepared to compete in the world of work and contribute to reducing unemployment.